2012
DOI: 10.1111/j.1524-4725.2011.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Small Animal Model for Soft Tissue Filler Characterization

Abstract: The rat subcutis model demonstrated the ability to differentiate between HA fillers with different residence times. The caliper-based rat-subcutis method demonstrated consistent volumetric analysis and correlated with human residence times of HA fillers. These quantitative results validate the rat subcutis model as an expedited preclinical model for HA fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…DiHMs (pH 5 and 7) were evaluated to determine their efficacy and safety in rats before clinical evaluation and commercialization. Previous experiments indicated that intradermal injections of soft tissue fillers in a rat model result in epidermal injury . Similar to the current study, subcutaneous injection of soft tissue fillers in a rat model to evaluate local effects after implantation is frequently used because of better efficiency and affordability …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…DiHMs (pH 5 and 7) were evaluated to determine their efficacy and safety in rats before clinical evaluation and commercialization. Previous experiments indicated that intradermal injections of soft tissue fillers in a rat model result in epidermal injury . Similar to the current study, subcutaneous injection of soft tissue fillers in a rat model to evaluate local effects after implantation is frequently used because of better efficiency and affordability …”
Section: Discussionsupporting
confidence: 70%
“…Previous experiments indicated that intradermal injections of soft tissue fillers in a rat model result in epidermal injury. 24 Similar to the current study, subcutaneous injection of soft tissue fillers in a rat model to evaluate local effects after implantation is frequently used because of better efficiency and affordability. 24 The crosslinked dextran used in this study was similar to previous dextranomer-based implants using a rat model with the exception of an HPMC suspension.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Volume retention of the grafts measured with a digital caliper allowed for continuous monitoring of graft volume over the course of the study rather than obtaining a single end-point value. 22 This approach allowed for the measurement of external factors such as skin thickness, which can increase as animals age. This is likely the reason why overall volume retention was high.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of volumetric maintenance, MRI techniques are an efficient method for measuring filler volume. 43,44 All of the fillers were easily detected and the three-dimensional structures were visualized by MRI owing to their high levels of hydration. 45 Pure HAc showed the brightest images because its main component is water.…”
Section: Volumetric Persistencementioning
confidence: 99%